2023
DOI: 10.1002/lary.30690
|View full text |Cite
|
Sign up to set email alerts
|

Triple Semicircular Canal Plugging versus Labyrinthectomy for Meniere Disease: A Retrospective Study

Abstract: ObjectivesThe study goals were to compare the long‐term efficacy of semicircular canal plugging (SCP) with labyrinthectomy in the treatment of advanced Meniere's disease (MD).Study DesignA retrospective study.SettingSingle tertiary medical center.MethodsA total of 116 MD patients (TSCP group of 90; labyrinthectomy group of 26) with complete medical documents in Shandong Provincial ENT Hospital, from March 2017 to March 2019 were retrospectively analyzed, including a battery of auditory and vestibular function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…TSCO is currently used with good curative effect. Based on the literature, the reported vertigo control rate ranges from 96.7–100% ( 6 , 29 ). The possible mechanism underlying might be associated with a reduction in movement of endolymph and minimizing hair cell stimulation during angular movement ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSCO is currently used with good curative effect. Based on the literature, the reported vertigo control rate ranges from 96.7–100% ( 6 , 29 ). The possible mechanism underlying might be associated with a reduction in movement of endolymph and minimizing hair cell stimulation during angular movement ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pre, Preoperative; 1 M, 1 month postoperatively; 6 M, 6 months postoperatively; and 18 M, 18 months postoperatively. (6,29). The possible mechanism underlying might be associated with a reduction in movement of endolymph and minimizing hair cell stimulation during angular movement (7).…”
Section: Figurementioning
confidence: 99%
“…Triple semicircular canal plugging (TSCP). A study with a total of 116 MD patients revealed that this technique was comparable to labyrinthectomy for the control of vertigo in intractable MD, representing an effective therapy [66].…”
Section: Treatment Of Ménière's Diseasementioning
confidence: 99%